Penerapan Pendekatan Matematika Realistik Untuk Meningkatkan Pemahaman Siswa SMK Swasta Kesehatan Baubau - Armin, Rismayani; Prasetyawan, L.M. Yogi (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2024)
This research is classroom action research with the problem formulation is whether the application of a realistic mathematical approach can improve the mathematical understanding of class X students at the Baubau Health Private Vocational School? This research aims to improve the mathematical understanding of class X students at the Baubau Health Private Vocational School through realistic application. This research was carried out on class X students at the Baubau Health Vocational School with a total of 23 students. Research data was obtained from observation sheets and tests for each cycle to see the increase in students' mathematical understanding after applying a realistic mathematical approach. This research was carried out in two cycles with stages (1) Planning, (2) Implementation of actions, (3) Observation and (4) Reflection. Based on the results of the analysis of student learning achievement data, the average student achievement score in the initial test, cycle I test and cycle II test was respectively 23.70; 54.78 and 75.65. Meanwhile, the percentage of classical completeness from the initial test results, cycle I test and cycle II test respectively was 17.39%; 56.52% and 100%. Based on the results of the research and discussion, it can be concluded that there has been an increase in students' understanding of three-dimensional learning through the application of a realistic mathematical approach in class X students at the Baubau Health Vocational School in odd semester academic year 2016/2017. Based on the conclusion of the research, it is suggested that: (1) Inquiry learning requires good time management and class management, so it is necessary to plan learning activities so that time is used more effectively. (2) When learning mathematics using the inquiry learning model, more varied problems should be given which enable students to improve their understanding of mathematics. (3) As a consideration in making policies to improve the quality of learning in schools, and for other researchers it is recommended to carry out similar research in more depth with different subjects and materials.